Prevalence of burnout, depression, anxiety and stress in Australian midwives: a cross-sectional survey. Issue 1 (December 2017) - Creedy, D.; Sidebotham, M.; Gamble, J.; Pallant, Julie; Fenwick, J.
Abstract Background The health and wellbeing of midwives are important considerations for workforce retention and quality care. The occurrence and relationships among mental health conditions such as burnout and depression have received little attention. We investigated the prevalence of burnout, depression, anxiety and stress in Australian midwives. Methods An online survey was conducted in September 2014. Participants were recruited through the Australian College of Midwives and professional networks. The survey sought personal and professional details. Standard measures included the Copenhagen Burnout Inventory (CBI) (Personal, Work and Client subscales), and Depression, Anxiety, and Stress Scale (DASS). The sample was collapsed into two groups according to DASS clinical cut-offs (normal/mild versus moderate/severe/extreme). Effect size statistics were calculated and judged according to Cohen's guidelines. Results One thousand thirty-seven surveys were received. Respondents were predominantly female (98%), with an average age of 46.43 years, and 16.51 years of practice. Using a CBI subscale cut-off score of 50 and above (moderate and higher), 64.9% (n = 643) reported personal burnout; 43.8% (n = 428) reported work-related burnout; and 10.4% (n = 102) reported client-related burnout. All burnout subscales were significantly correlated with depression, anxiety and stress, particularly personal and work-related burnout with Spearman's rho correlations ranging from .51 to .63 (p < .001). Around 20% of midwives reported moderate/ severe/ extreme levels of depression (17.3%); anxiety (20.4%), and stress (22.1%) symptoms. Mann-Whitney U tests revealed significant differences between groups with depression (r = .43), anxiety (r = .41) and stress (r = 48) having a medium size effect on burnout. Conclusion Prevalence of personal and work-related burnout in Australian midwives was high. The physical and psychological exhaustion associated with the different types of burnout were reflected in symptoms of depression, anxiety and stress symptoms. Further research is needed to support the personal well-being of midwives and minimize workplace burnout by developing short and long term strategies.